Implementasi Model Pembelajaran Sentra Di TK Negeri Pembina 1 Palembang - Pera Renda; Hasmalena hasmalena; sri sumarni (FKIP Universitas sriwijaya, 2017)
This study aims to describe the implementation of learning center model in TK Negeri Pembina 1 Palembang, which includes: (1) learning planning, (2) implementation of learning and (3) assessment of learning outcomes in learning center model in TK Negeri Pembina 1 Palembang. The type of research used is descriptive research with quantitative approach. Subjects in this study were principals, teachers and children kindergarten groups A and B. Data collection in this study was conducted through interviews, observation and documentation. During the research, researchers record the learning process and fill out the teacher's observation sheet of the assessment of the implementation of learning. Interviews were conducted to school principals and teachers on learning center models. From the result of observation for learning planning conducted by teacher for 4 meetings get the average value 79,68 which included in good category. Implementation of learning conducted by teachers for 4 meetings got an average rating of 87.5 which is included in the category very well. Assessment of learning outcomes conducted by teachers during the four meetings obtained an average score of 83.33 which is classified as very good. From the results of research and discussion can be concluded that the learning center model implemented in TK Negeri Pembina 1 Palembang is in accordance with the existing theories.